On the non-destructive measurement of local mass transfer using X-ray computed tomography. (February 2015) - Wang, D.; Huang, Y.; Ewing, D.; Chow, T.; Cotton, J.; Noseworthy, M.D.; Ching, C.Y.
Abstract: A novel methodology is developed here to measure wall mass transfer rates non-destructively using X-ray computed tomography (CT). The mass transfer was measured using a gypsum lined 203 mm diameter straight pipe section using a dissolving wall method to water. The measurements were performed at a Reynolds number of 86, 000 and Schmidt number of 1200. The local wear of the internal surface is obtained from the CT scans by aligning and analyzing the cross-sectional scanned images of the test section before and after the experiment. The full surface wear contours and the corresponding mass transfer rates are obtained by a three-dimensional reconstruction of the entire test section. The measurements from the CT scans are compared to results obtained from ultrasonic (UT) measurements of the wall thickness and internal surface measurements using a Coordinate Measuring Machine (CMM) and digital laser scans. The results from the CT scan methodology are in good agreement with the other methods, indicating that the method is robust and can be used to obtain the local mass transfer and roughness over the entire surface. Thus, it can be used as a principal method to investigate mass transfer non-intrusively in complex piping geometries.